Effects of calcium peroxide on growth of Pontederia cordata and water quality - Xiaowen Lin; Mengdie Zhou; Xiaodong Wu; Xuguang Ge; Rui Xu; Shuang Peng; Mengting Gong; Jinge Li; Wenhui Li (Journal of Freshwater Ecology)
Combined chemical-biological methods play an important role in ecological restoration. However, it is still unknown whether the addition of calcium peroxide (CaO2) can promote the growth of Pontederia cordata (P. cordata) and the improvement of water quality. Effects of different levels of added CaO2 (0, 0.2, 0.4, 0.6, 0.8, 1, and 2 kg/m2) on P. Cordata growth and water quality were investigated. CaO2 promoted germination and tillering and increased the leaf number (p < 0.05) of P. cordata, but reduced leaf length. The plant height and leaf width increased only when the added CaO2 levels were 0.6 kg/m2 and 1 kg/m2, respectively. Adding 0.4–0.6 kg/m2 CaO2 had a cumulative effect on the biomass. High levels of added CaO2 (2 kg/m2) affected the physiology of P. cordata resulting in the most serious damage to cell membrane lipids, the lowest catalase activity, and the highest chlorophyll content. Adding CaO2 did not cause DO and pH of the water to be too high for a long time, but excessive CaO2 made TN and CODMn too high. Thus, 1 kg/m2 CaO2 was most conducive to the growth of P. cordata and the improvement of water quality.